Affinity and Adverse the Contemporary Comprehension of the Disposition of Transactional and Transformational Leadership - Nikijuluw, Reynold Pieter Jordan Vigeleyn; Persulessy, Sylvia Irene; Jakob, Juvrianto Chrissunday (P3M POLITEKNIK NEGERI AMBON, 2024)
This research, explores the interaction between two dominant leadership styles—transactional and transformational leadership—in modern organizational contexts. The study examines the affinities where these styles complement each other and the adversities that arise from their inherent differences. Through a detailed analysis of existing literature, this research highlights how transactional leadership is effective in ensuring operational stability and short-term goal attainment, while transformational leadership drives innovation, employee engagement, and long-term organizational change. The findings suggest that a synergistic approach, combining both leadership styles, can yield optimal results in complex environments. However, challenges arise when leaders switch between these contrasting approaches, leading to potential conflicts in motivation and employee satisfaction. This research concludes that leaders who can navigate both styles with flexibility are better equipped to meet the demands of contemporary organizations. The study offers insights into leadership development, emphasizing the need for adaptability in managing both structured tasks and inspiring change